2016
DOI: 10.4238/gmr.15038336
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cisplatin resistance in non-small cell lung cancer stem cells by Taxus chinensis var.

Abstract: ABSTRACT. Drug resistance in cells is a major impedance to successful treatment of lung cancer. Taxus chinensis var. inhibits the growth of tumor cells and promotes the synthesis of interleukins 1 and 2 and tumor necrosis factor, enhancing immune function. In this study, T. chinensis var.-induced cell death was analyzed in lung cancer cells (H460) enriched for stem cell growth in a defined serum-free medium. Taxus-treated stem cells were also analyzed for Rhodamine 123 (Rh-123) expression by flow cytometry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…DU145 Tax-Res exosomes were enriched for MDR-1, MDR-3, Endophilin-A2, and PABP4. [190] Additionally, docetaxel-sensitive PCa cells (DU145, 22Rv1, and LNCaP) developed resistance to docetaxel after exposure to docetaxel-resistant DU145 and 22Rv1 variants (DU145RD and 22Rv1RD), with docetaxel-resistant DU145RD and 22Rv1RD miR-31-5p Sutitinib Effects on tyrosine kinase receptor expression [170] miR-549a TKI Promotes angiogenesis and endothelial migration [171] LncRNAIGFL2-AS1 Sutitinib Enhances tumor cell autophagy [180] RAB27B Sutitinib Promotes angiogenesis and anti-apoptosis [199] LncRNAKIF9-AS1 Sutitinib Enhances tumor cell autophagy [178] BC microRNA-148b-3p PTX, DOX Anti-tumor apoptosis [174] LINC00355 Cisplatin Promotes drug efflux [179] PCa miR-423-5p Taxane Promotes epithelial-mesenchymal transition [175] miR-27a Cisplatin, DOX, DTX Anti-tumor apoptosis [172] circSFMBT2 DTX Anti-tumor apoptosis [183] CD44v8-10 mRNA DTX Promotes the transformation of cellular plasticity [184] lincROR DTX Anti-tumor apoptosis [201] Circ-XIAP DTX Anti-tumor apoptosis [182] p-gp/ MDR-1 Enzalutamide Promotes drug efflux [165] YAP1 Enzalutamide Inhibits autophagy and affects AR signaling [189] BRN4 mRNA Enzalutamide Anti-tumor apoptosis [185] BRN2 mRNA Enzalutamide Anti-tumor apoptosis [185] ATP2B1/PMCA ATPase Enzalutamide Affects AR signaling [191] caveolin-1 Enzalutamide Affects cellular metabolism and autophagy [192] AR-V7 RNA Enzalutamide, Abiraterone Affects AR signaling [186,187] EVs inducing resistance in docetaxel-sensitive PCa cells, possibly through the release of MDR-1/P-gp transporter proteins. [164] EVs secreted by docetaxel-resistant PC3 cells exhibited higher levels of EV P-gp than PC3 cell exosomes.…”
Section: Proteinsmentioning
confidence: 99%
“…DU145 Tax-Res exosomes were enriched for MDR-1, MDR-3, Endophilin-A2, and PABP4. [190] Additionally, docetaxel-sensitive PCa cells (DU145, 22Rv1, and LNCaP) developed resistance to docetaxel after exposure to docetaxel-resistant DU145 and 22Rv1 variants (DU145RD and 22Rv1RD), with docetaxel-resistant DU145RD and 22Rv1RD miR-31-5p Sutitinib Effects on tyrosine kinase receptor expression [170] miR-549a TKI Promotes angiogenesis and endothelial migration [171] LncRNAIGFL2-AS1 Sutitinib Enhances tumor cell autophagy [180] RAB27B Sutitinib Promotes angiogenesis and anti-apoptosis [199] LncRNAKIF9-AS1 Sutitinib Enhances tumor cell autophagy [178] BC microRNA-148b-3p PTX, DOX Anti-tumor apoptosis [174] LINC00355 Cisplatin Promotes drug efflux [179] PCa miR-423-5p Taxane Promotes epithelial-mesenchymal transition [175] miR-27a Cisplatin, DOX, DTX Anti-tumor apoptosis [172] circSFMBT2 DTX Anti-tumor apoptosis [183] CD44v8-10 mRNA DTX Promotes the transformation of cellular plasticity [184] lincROR DTX Anti-tumor apoptosis [201] Circ-XIAP DTX Anti-tumor apoptosis [182] p-gp/ MDR-1 Enzalutamide Promotes drug efflux [165] YAP1 Enzalutamide Inhibits autophagy and affects AR signaling [189] BRN4 mRNA Enzalutamide Anti-tumor apoptosis [185] BRN2 mRNA Enzalutamide Anti-tumor apoptosis [185] ATP2B1/PMCA ATPase Enzalutamide Affects AR signaling [191] caveolin-1 Enzalutamide Affects cellular metabolism and autophagy [192] AR-V7 RNA Enzalutamide, Abiraterone Affects AR signaling [186,187] EVs inducing resistance in docetaxel-sensitive PCa cells, possibly through the release of MDR-1/P-gp transporter proteins. [164] EVs secreted by docetaxel-resistant PC3 cells exhibited higher levels of EV P-gp than PC3 cell exosomes.…”
Section: Proteinsmentioning
confidence: 99%
“…[10,11] Notably, TC exerts specific curative effects by inhibiting the progression, metastasis, recurrence, and reversal of drug resistance in NSCLC and is nontoxic to normal noncancerous cells in vitro and nude mice in vivo. [12–14] These findings suggest that TC may serve as a promising, safe, economical, and effective adjuvant or a drug for NSCLC treatment. However, owing to its multitarget, multicomponent, and multilevel characteristics, elucidating the efficacy and mechanism of action of TC against NSCLC is challenging using traditional research methods.…”
Section: Introductionmentioning
confidence: 97%
“…Until the extraction of Taxol with a broad-spectrum anti-tumor effect from Taxus L. plant in the 1970s, TW has been widely concerned for its pharmacological value ( Wani et al, 1971 ). Currently, abundant evidence has confirmed that the extract of TW is able to inhibit proliferation, induce apoptosis, strengthen immunity, and reverse drug resistance in lung cancer cells ( Jiang et al, 2016 ; Zhang et al, 2021a ). However, the function and the underlying mechanism of TW in preventing or reversing cancer metastasis have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%